(untitled) (Journal of Geography and Environmental Management, 2025)
Land degradation and ecosystem imbalance remain major environmental challenges in Kazakhstan, particularly in post-technogenic and radiation-affected territories. The Semipalatinsk Nuclear Test Site represents a unique area for studying long-term landscape transformation and recovery. This research aims to evaluate land degradation and surface moisture variability between 2019 and 2025 using Sentinel-2 remote sensing data. The methodology integrates the calculation of key spectral indices - SWIR, NDWI, NDVI, and MSI - to assess vegetation dynamics, moisture content, and surface dryness. Results indicate a noticeable increase in NDVI and NDWI and a decrease in MSI and SWIR, confirming the improvement of soil moisture and vegetation recovery, along with a reduction in aridity. The area of moist and vegetated lands expanded by approximately 20 - 25 %, demonstrating active natural renaturation processes. The study highlights the effectiveness of Sentinel-2 multispectral monitoring for ecological rehabilitation assessment in post-technogenic regions of Kazakhstan. The findings contribute to sustainable land management and environmental monitoring in arid landscapes.